Accuracy Where It Matters: Brady v. Maryland in the Plea Bargaining Context - Corinna Barrett Lain (Washington University Law Quarterly, 2002)
Decided in 1963, Brady v. Maryland imposes on prosecutors a duty to share with defendants information favorable to the defense and material to guilt or punishment. Under Brady and its progeny, prosecutors must disclose impeachment as well as exculpatory information, and are not excused from nondisclosure even if they never received a request for the information or were unaware that the government had it to give. In the analysis below, I argue that Brady’s role in protecting the innocent from wrongful conviction is just as essential in the plea bargaining context as it is at trial, and that therefore even defendants who plead guilty should be entitled to Brady’s protections. Part I of this Article examines the judicial approaches currently used to extend Brady rights to defendants who plead guilty, concluding that the strongest doctrinal justification for applying Brady in the plea bargaining context looks to Brady’s effect on the accuracy of a plea. Part II examines Brady’s effect on the accuracy of guilty pleas, concluding that the disclosure of material, favorable information is necessary to prevent innocent defendants from falsely pleading guilty. Part III turns to Brady’s materiality standard in the plea bargaining context, arguing that the showing currently required for post-plea Bradyclaims fails to realize Brady’s accuracy-enhancing potential. Part IV concludes the analysis, underscoring the importance of protecting innocent defendants who plea bargain as well as those who contest their guilt at trial.
Keywords: Plea bargaining; Criminal procedure; Discovery (Law); Brady v. Maryland 373 U.S. 83 (1963); Guilty pleas